The relationship between serum lipids and sudden sensorineural hearing loss: a systematic review and meta-analysis. - I Jen Chang; Chung Jan Kang; Chen Yu Yueh; Ku Hao Fang; Re Ming Yeh; Yao Te Tsai (PLoS ONE)
Background Sudden sensorineural hearing loss (SSNHL) is a relatively common condition that is usually of unknown etiology. A number of individual studies have investigated the association between various serum lipids and SSNHL; however, the findings have been inconsistent. In an attempt to obtain more definitive information on the relationship between serum lipids and SSNHL, we carried out a systematic review and meta-analysis. Methods Medline, the Cochrane Library, and EMBASE were searched using the following key words: lipid, cholesterol, triglyceride, fat, serum, blood, sudden hearing loss, hearing loss, hearing disorders. Randomized controlled trials, prospective cohort studies, and retrospective case-control studies involving patients with SSNHL and healthy controls that examined the relationship (reported as odds ratios [OR]) between lipid profiles and SSNHL were included. Primary outcomes were total cholesterol and low-density lipoprotein cholesterol (LDL-C) concentrations. Secondary outcomes were triglyceride, high-density lipoprotein cholesterol, and lipoprotein(a) concentrations. Results A total of 6 case-control studies were included in this systematic review/meta-analysis. The total number of participants ranged from 30 to 250 in the case group and from 43 to 271 in the control group. Meta-analysis revealed no significant difference in total cholesterol levels between the case and control groups (pooled OR = 1.79, 95% confidence interval [CI] = 0.98 to 3.26, P = 0.057). Likewise, meta-analysis revealed no significant difference in LDL-C concentrations between the case and control groups (pooled OR = 1.15, 95% CI = 0.64 to 2.07, P = 0.639). Since there were an insufficient number of studies reporting data for the secondary outcomes, meta-analysis was not possible. Conclusions Our results do not provide evidence for serum lipids being associated with SSNHL, nor do they definitively rule out such an association. Additional studies are needed to ascertain the relationship, or lack thereof, between serum lipids and SSNHL.